2007
DOI: 10.4141/p05-103
|View full text |Cite
|
Sign up to set email alerts
|

Performance of short-lived perennial grasses grown with and without alfalfa at a semiarid location in southern Saskatchewan

Abstract: R. 2007. Performance of short-lived perennial grasses grown with and without alfalfa at a semiarid location in southern Saskatchewan. Can. J. Plant Sci. 87: 59-65. Tyically, crop rotations in the semiarid region of the Canadian prairies do not include perennial forages because forage termination produces negative effects on subsequent annual crops. Three short-lived perennial grass species, Dahurian wildrye grass (Elymus dahuricus Turcz. Ex Griseb), intermediate wheatgrass [Elytrigia intermedia (Host) Nevski] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…The significant decline of monoculture grass DMY after the second production year, under both the twocut and three-cut management systems, can probably be attributed to the depletion of soil N in the monoculture grass plots during the course of this study. This possible explanation of the better performance of grassÁalfalfa mixtures over monoculture grasses was also mentioned by Jefferson et al (2007). The increase in the proportion of alfalfa and consequent decrease in the proportion of the grass component in the simple, CM and VCM grassÁ alfalfa mixture plots (assessed only in the two-cut system) also could have been due to an inadequate supply of soil N for the grass component in the mixtures after the second production year.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The significant decline of monoculture grass DMY after the second production year, under both the twocut and three-cut management systems, can probably be attributed to the depletion of soil N in the monoculture grass plots during the course of this study. This possible explanation of the better performance of grassÁalfalfa mixtures over monoculture grasses was also mentioned by Jefferson et al (2007). The increase in the proportion of alfalfa and consequent decrease in the proportion of the grass component in the simple, CM and VCM grassÁ alfalfa mixture plots (assessed only in the two-cut system) also could have been due to an inadequate supply of soil N for the grass component in the mixtures after the second production year.…”
Section: Discussionmentioning
confidence: 78%
“…Simple mixtures of two to four species may offer the best means to provide plant diversity and yet limit seedling competition (Alberta Agriculture and Rural Development 2005). Jefferson et al (2007), in a study done at Swift Current, Saskatchewan, Canada, a semiarid environment, concluded that three introduced grass species produced more forage when grown in mixture with alfalfa than as monoculture. A recent study done at Swift Current (dry-mixed grassland ecoregion) and Saskatoon (moist-mixed grassland ecoregion), Saskatchewan, has shown that western wheatgrass (Pascopyrum smithii Rydb.)…”
mentioning
confidence: 99%
“…Perennial forages contribute to enhanced soil health and pest suppression, both of which can provide benefits to subsequent crops (Entz et al 2002 and references therein;Olmstead and Brummer 2008;Meiss et al 2010). Moisture availability is a major determinant of forage-related benefits, since moisture depletion by perennial forages can reduce yield of subsequent crops in dry regions ; however, no-till establishment and termination of perennial forage stands can allow their successful integration in more arid regions of the prairies (Jefferson et al 2007). Water use by forages can be beneficial for dewatering soils in regions with excess moisture and for salinity management .…”
Section: Perennial Crops In Rotationmentioning
confidence: 99%
“…However, the total DMY of SWG in mixture with 'Beaver' alfalfa (3.5 Mg ha −1 ) at Swift Current, SK, [38] on a non-saline soil was comparable with the yields obtained in the current study, and those of 'VNS' smooth brome in mixture with '55V48 alfalfa (5.1 Mg ha −1 ) in North Dakota, USA, [39] and of alfalfa + SBG mixture grown in the Mediterranean region of Turkey (2.6-3.3 Mg ha −1 ) [40] were higher and comparable, respectively.…”
Section: Stand Establishment Botanical Composition and Forage Yield O...mentioning
confidence: 96%
“…Ex Griseb], intermediate wheatgrass [Elytrigia intermedia (Host) Nevski], and slender wheatgrass [Elymus trachycaulus (Link.) Gould ex Shinners] were grown with alfalfa, the grasses produced similar forage yield and yield compensation by alfalfa grown with Dahurian wildrye and slender wheatgrass produced similar total forage yield [38].…”
Section: Stand Establishment Botanical Composition and Forage Yield O...mentioning
confidence: 97%